A Randomized, Placebo-Controlled Clinical Trial of Bamlanivimab and Etesevimab Together in High-Risk Ambulatory Patients With COVID-19 and Validation of the Prognostic Value of Persistently High Viral Load. (28th October 2021) - Dougan, Michael; Azizad, Masoud; Mocherla, Bharat; Gottlieb, Robert L; Chen, Peter; Hebert, Corey; Perry, Russell; Boscia, Joseph; Heller, Barry; Morris, Jason; Crystal, Chad; Igbinadolor, Awawu; et al.
Abstract: Background: Based on interim analyses and modeling data, lower doses of bamlanivimab and etesevimab together (700/1400 mg) were investigated to determine optimal dose and expand availability of treatment. Methods: This Phase 3 portion of the BLAZE-1 trial characterized the effect of bamlanivimab with etesevimab on overall patient clinical status and virologic outcomes in ambulatory patients ≥12 years old, with mild-to-moderate coronavirus disease 2019 (COVID-19), and ≥1 risk factor for progressing to severe COVID-19 and/or hospitalization. Bamlanivimab and etesevimab together (700/1400 mg) or placebo were infused intravenously within 3 days of patients' first positive COVID-19 test. Results: In total, 769 patients were infused (median age [range]; 56.0 years [12, 93], 30.3% of patients ≥65 years of age and median duration of symptoms; 4 days). By day 29, 4/511 patients (0.8%) in the antibody treatment group had a COVID-19-related hospitalization or any-cause death, as compared with 15/258 patients (5.8%) in the placebo group (Δ[95% confidence interval CI] = −5.0 [−8.0, −2.1], P < .001). No deaths occurred in the bamlanivimab and etesevimab group compared with 4 deaths (all COVID-19-related) in the placebo group. Patients receiving antibody treatment had a greater mean reduction in viral load from baseline to Day 7 (Δ[95% CI] = −0.99 [−1.33, −.66], P < .0001) compared with those receiving placebo. Persistently high viral load at Day 7 correlated with COVID-19-related hospitalization or any-cause death by Day 29 in all BLAZE-1 cohorts investigated. Conclusions: These data support the use of bamlanivimab and etesevimab (700/1400 mg) for ambulatory patients at high risk for severe COVID-19. Evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants will require continued monitoring to determine the applicability of this treatment. Clinical Trials Registration: NCT04427501. Abstract : Bamlanivimab and etesevimab together (700 mg plus 1400 mg) reduced coronavirus disease 2019 (COVID-19)-related hospitalizations and viral load in patients with mild-to-moderate COVID-19, with persistently high viral load correlating with COVID-19-related hospitalizations or any-cause death.